Gender specific perspectives among smallholder farm households on water-energy-food security nexus issues in Ethiopia - Grace Ballesfin Villamor; Dawit Diriba Guta; Utkur Djanibekov; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2018)
The water-energy-food security nexus concept is a widely recognized analytical approach to consider and achieve sustainable development goals. However, the water-energy-food security nexus concept has mostly been analyzed at higher scales in a top-down manner, while examples of bottom-up and local scale applications remain limited. Breaching this gap, the research presented in this paper describes and assesses the water-energy-food nexus from a smallholder farm household perspective in the context of rural Ethiopia through a gender-specific lens. We adopted the "Actors, Resources, Dynamics and Interactions" participatory approach to co-develop a mental model of this nexus concept. Using this approach, we were able to examine the key elements and interlinkages among major nexus related resources that affect management according to gender. The results indicate that there are four aspects that differentiate between male and female farm household management with respect to the water-energy-food nexus. These differences include gender specific productive roles, perceptions of target resources, access to external actors, and decision making with respect to target resource management and utilization, which may affect the dynamics and governance of important components of the water-energy-food nexus.
Keywords: Q; 330; ARDI method; bottom-up approach; energy-food-land linkages; gender roles; intra-household heterogeneity; mental model